Looking back at prospective modeling of outbreak response strategies for managing global type 2 oral poliovirus vaccine (OPV2) cessation - Kimberly M. Thompson; Dominika A. Kalkowska; Kamran Badizadegan (Frontiers Media S.A., 2023)
IntroductionDetection of poliovirus transmission and ongoing oral poliovirus vaccine (OPV) use continue to delay poliomyelitis eradication. In 2016, the Global Polio Eradication Initiative (GPEI) coordinated global cessation of type 2 OPV (OPV2) for preventive immunization and limited its use to emergency outbreak response. In 2019, GPEI partners requested restart of some Sabin OPV2 production and also accelerated the development of a genetically modified novel OPV2 vaccine (nOPV2) that promised greater genetic stability than monovalent Sabin OPV2 (mOPV2).MethodsWe reviewed integrated risk, economic, and global poliovirus transmission modeling performed before OPV2 cessation, which recommended multiple risk management strategies to increase the chances of successfully ending all transmission of type 2 live polioviruses. Following OPV2 cessation, strategies implemented by countries and the GPEI deviated from model recommended risk management strategies. Complementing other modeling that explores prospective outbreak response options for improving outcomes for the current polio endgame trajectory, in this study we roll back the clock to 2017 and explore counterfactual trajectories that the polio endgame could have followed if GPEI had: (1) managed risks differently after OPV2 cessation and/or (2) developed nOPV2 before and used it exclusively for outbreak response after OPV2 cessation.ResultsThe implementation of the 2016 model-based recommended outbreak response strategies could have ended (and could still substantially improve the probability of ending) type 2 poliovirus transmission. Outbreak response performance observed since 2016 would not have been expected to achieve OPV2 cessation with high confidence, even with the availability of nOPV2 prior to the 2016 OPV2 cessation.DiscussionAs implemented, the 2016 OPV2 cessation failed to stop type 2 transmission. While nOPV2 offers benefits of lower risk of seeding additional outbreaks, its reduced secondary spread relative to mOPV2 may imply relatively higher coverage needed for nOPV2 than mOPV2 to stop outbreaks.